RESPON KONSENTRASI TIENS GOLDEN HARVEST TERHADAP PERTUMBUHAN DAN PRODUKSI KENTANG (Solanum tuberossum L) DENGAN MENGGUNAKAN UKURAN BENIH G3 YANG BERBEDA - Sumatera Tarigan; Meriksa Sembiring; Riduan Sembiring (Universitas Quality, 2019)
This study aims to determine the effect of the number of tubers / kg of seeds and the dose of biological liquid fertilizer on the growth and production of potato plants. The research was carried out at the Quality University Experimental Garden in Karo District at + 2140 m asl which was conducted from June 2017 - September 2017. This study used Factorial Randomized Group Design with two treatment factors. The first factor is the size of seed bulbs with four levels, namely: 7 tubers / kg (P1); 14 tubers / kg (P2) and 21 tubers / kg (P3), and the second factor is the liquid fertilizer dosage with four levels: 0.0 ml / l water (Ho); 0.2 ml / l water (H1); 0.4 ml / l water (H2); 0.8 ml / l water (H3). The results showed that the treatment of tuber size as seeds significantly affected the number of tubers / samples of production / samples, production / plots, but not significantly different for plant height, number of branches. The treatment of biological liquid fertilizer doses significantly affected plant height, tuber / sample number, production / sample, production / plot. But it was not significant for the number of branches. The interaction between the two treatment factors did not significantly affect all parameters observed throughout the study.